Development of managerial and Information Technology skills in Learning Factories in the context of Industry 4.0: a case study - Antonio de Albuquerque Felizola Romeral, Pedro; de Mesquita Spinola, Mauro; Franco Gonçalves, Rodrigo; Zancul, Eduardo (Revista Gestão da Produção Operações e Sistemas, 2021)
Purpose – This paper aims to analyze the most relevant and present technologies in Learning Factories, to analyze how these technologies can be integrated and how to analyze how this environment operates given the shortage of a specialist workforce. Theoretical framework - The new technological landscape, also known as Industry 4.0, requires trained personnel to operate, interpret, and make decisions given the new tools. This means that training the professionals who will work in the industries need to come into contact with all this existing Information Technology (IT) architecture and skills need to be encouraged to be developed to allow these professionals to work effectively. One way to act on these fronts is through Learning Factories, which are integrated environments for Industry 4.0 training and the development of technology, applications, and transfer them to industry. Despite recognizing this strategy, there is no explicit discussion on how IT architecture is built, how these technologies are integrated, and which teaching strategies are effective in Learning Factories. Design/methodology/approach - A case study was carried out at a Learning Factory in a Brazilian state university, called ‘Fábrica do Futuro’, describing the present IT systems, their relevance in student education and the teaching strategies adopted, compared with the theoretical sample presented. Findings – A need was identified to explore the integration between all technologies, involving tools, such as 3D printing, radio frequency identification (RFID), Computer Vision and systems such as ERP, MES and PLM. The development of communication, leadership, and problem-solving skills needs to be encouraged for effective learning and adequate operation of these technologies. Originality/Value - This study aims to contribute to universities and research institutions that wish to implant and/or operationalize a Learning Factory, presenting and discussing a possible IT structure and the skills developed with it. Keywords - Learning Factory. Industry 4.0. Information Technologies. ERP. 3D printing.